1989
DOI: 10.1111/j.1476-5381.1989.tb12607.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological properties of a C‐fibre response evoked by saphenous nerve stimulation in an isolated spinal cord‐nerve preparation of the newborn rat

Abstract: The saphenous nerve-evoked slow v.r.p. was depressed by [Met5] enkephalin (0.1-1 EM), dynorphin (1-13X0.2 gM) and morphine (1-2 pM), and these effects were reversed by naloxone (1 pM).6 Two endogenous peptides, galanin (1-2 pM) and somatostatin (1-2.5 pM), inhibited the slow v.r.p. evoked by saphenous nerve stimulation, whereas another endogenous peptide, calcitonin generelated peptide (0.1-0.5 pM), potentiated the slow v.r.p. The slow v.r.p. was also inhibited by yaminobutyric acid (GABA, 20pM) and muscimol (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 44 publications
3
40
0
Order By: Relevance
“…Finally, it is possible that spantide activates an alternative receptor that mediates an overriding vasoconstriction or blocks the capsaicin receptor. The presence of more than one type of spantide-susceptible tachykinin receptor has been previously suggested (Chahl, 1985;Featherstone, Fosbraey & Morton, 1986;Buck & Shatzer, 1988;Nussbaumer, Yanagisawa & Otsuka, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is possible that spantide activates an alternative receptor that mediates an overriding vasoconstriction or blocks the capsaicin receptor. The presence of more than one type of spantide-susceptible tachykinin receptor has been previously suggested (Chahl, 1985;Featherstone, Fosbraey & Morton, 1986;Buck & Shatzer, 1988;Nussbaumer, Yanagisawa & Otsuka, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the slow VRPs induced by both saphenous nerve stimulation and application of capsaicin to skin were markedly depressed by a tachykinin antagonist spantide (Nussbaumer et al, 1989;Yanagisawa et al, 1992). There is evidence that these slow depolarizing responses represent a component of nociceptive spinal reflexes (Nussbaumer et al, 1989;Yanagisawa et al, 1992). (Yoshioka et al, 1990b), these concentrations would be sufficiently high to block other types of muscarinic receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated spinal cord-saphenous nerve preparation The hemisected spinal cord below the middle thoracic level was isolated together with the attached L3-L5 ventral roots and dorsal roots, the latter remaining connected with the dorsal root ganglia and the femoral and saphenous nerves (Nussbaumer et al, 1989). The saphenous nerve was stimulated supramaximally with one to five pulses of 500 ys duration and 30-40 V intensity at 50 Hz and the potential changes were recorded from the L3 ventral root on a pen recorder.…”
Section: Preparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This preparation enables us to obtain stable extracellular recording from ventral roots and thus to carry out detailed pharmacological analyses of both responses to nerve stimulation and responses to exogenously applied agents. Activation of primary afferent fibres by either electrical stimulation at C-fibre strength or peripheral noxious stimulation evokes a depolarization of a slow time course in ventral roots and this depolarization is markedly depressed by tachykinin antagonists as well as opioid agonists (Akagi et al, 1985;Otsuka & Yanagisawa, 1988;Nussbaumer et al, 1989;Yanagisawa et al, 1992;Guo et al, 1993;Hosoki et al, 1994). These and other lines of evidence suggest that this depolarization, hereafter referred to as the slow ventral root potential (VRP), represents a C-fibre-evoked nociceptive response in which tachykininergic primary afferents are involved (Otsuka & Yanagisawa, 1987).…”
Section: Introductionmentioning
confidence: 99%